LOX Gene Transcript Accumulation in Olive (Olea europaea L.) Fruits at Different Stages of Maturation: Relationship between Volatile Compounds, Environmental Factors, and Technological Treatments for Oil Extraction. (1st May 2012) - Muzzalupo, Innocenzo; Macchione, Barbara; Bucci, Cristina; Stefanizzi, Francesca; Perri, Enzo; Chiappetta, Adriana; Tagarelli, Antonio; Sindona, Giovanni
Abstract : The quality of olive oil is influenced by genetic and environmental factors and by the maturation state of drupes, but it is equally affected by technological treatments of the process. This work investigates the possible correlation between olive LOX gene transcript accumulation, evaluated in fruits collected at different stages of maturation, and chemical biomarkers of its activity. During olive fruit ripening, the same genotype harvested from two different farms shows a positive linear trend between LOX relative transcript accumulation and the content of volatile compounds present in the olive oil aroma. Interestingly, a negative linear trend was observed between LOX relative transcript accumulation and the content of volatile compounds present in the olive pastes obtained from olive fruits with and without malaxation. The changes in the olive LOX transcript accumulation reveal its environmental regulation and suggest differential physiological functions for the LOXs.